2022
DOI: 10.1002/jlb.3mr0322-692rr
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis, pyruvate, and mitochondria energy supply chain shortage

Abstract: Balancing high energy-consuming danger resistance and low energy supply of disease tolerance is a universal survival principle that often fails during sepsis. Our research supports the concept that sepsis phosphorylates and deactivates mitochondrial pyruvate dehydrogenase complex control over the tricarboxylic cycle and the electron transport chain. StimulatIng mitochondrial energetics in septic mice and human sepsis cell models can be achieved by inhibiting pyruvate dehydrogenase kinases with the pyruvate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…With PDC-E2 being an integral part of the mitochondrial pyruvate dehydrogenase complex, we started exploring functional consequences of the NAP1L1–PDC-E2 interaction. Several studies demonstrated that the mitochondrial pyruvate dehydrogenase complex gets dysregulated due to septic host environment [ 58 , 59 ]. Although anucleate, emerging data demonstrates that the human PLT transcriptome is not static.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With PDC-E2 being an integral part of the mitochondrial pyruvate dehydrogenase complex, we started exploring functional consequences of the NAP1L1–PDC-E2 interaction. Several studies demonstrated that the mitochondrial pyruvate dehydrogenase complex gets dysregulated due to septic host environment [ 58 , 59 ]. Although anucleate, emerging data demonstrates that the human PLT transcriptome is not static.…”
Section: Resultsmentioning
confidence: 99%
“…The immunometabolism during sepsis is characterized by a switch from a high-energy infection resistance mode to a low-energy conservation tolerance mode within 4–8 h after sepsis dissemination [ 58 ]. The pyruvate dehydrogenase complex acts as an energy homeostat, and its deactivation creates an energy supply chain shortage during sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a septic mouse model, DCA treatment was found to reverse shock, reduce hepatocyte injury, significantly improve hyperlactatemia and immune paralysis, and significantly improve septic survival. 75 Mitochondrial homeostasis plays a decisive role in regulating cellular energy metabolism and signaling pathways. PPAR-γ coactivator 1 alpha (PGC-1α) is one of the most important transcription factors that can drive mitochondrial biogenesis to respond to external stimuli and maintain mitochondrial homeostasis.…”
Section: Characteristics Of Mitochondria In the Metabolic Modulation ...mentioning
confidence: 99%